Trends in fixed income : investing in bonds - Lydon, Tom, 1960- (FT Press Delivers elements., 2010)
"Understanding today's bond market-and using it to increase your returns while managing your risk. If you liked this Element, read more from Tom Lydon, including The ETF trend following playbook: profiting from trends in bull or bear markets with exchange traded funds (ISBN: 9780137029013)"--Resource description page.